D-Penicillamine and bovine serum albumin co-stabilized copper nanoclusters with remarkably enhanced fluorescence intensity and photostability for ultrasensitive detection of Ag+. (26th November 2015) - Ruiyi, Li; Huiying, Wang; Xiaoyan, Zhou; Xiaoqing, Liao; Xiulan, Sun; Zaijun, Li
Abstract : This study reports the synthesis ofd -penicillamine and bovine serum albumin co-stabilized copper nanoclusters. The nanoclusters show high fluorescence intensity, stability and response towards silver ion. Abstract : Copper nanoclusters (CuNCs) have become promising nanomaterials due to their excellent electronic conductivity and biocompatibility. In this study, we reported a facile synthesis ofd -penicillamine and bovine serum albumin co-stabilized copper nanoclusters (BSA/DPA–CuNCs) and the use as optical probe for the detection of Ag + . Herein, Cu 2+ was reduced into Cu 0 byd -penicillamine, further leading to form DPA–CuNCs. Then, BSA was introduced into DPA–CuNCs to obtain BSA/DPA–CuNCs by their electrostatic attraction. The as-prepared BSA/DPA–CuNCs exhibit remarkably enhanced fluorescence intensity and photostability. The peak fluorescence intensity is more than 2-fold that of DPA–CuNCs. Due to the synergistic effect between DPA and BSA, the nanosensor based on BSA/DPA–CuNCs gives ultrasensitive fluorescence response towards Ag + . Its peak fluorescence intensity linearly decreases with the increase of Ag + concentration in the range of 1.0 × 10 −8 to 1.0 × 10 −16 M with the detection limit of 4.3 × 10 −17 M (S/N = 3). The method provides the advantage of sensitivity, repeatability and stability. It has been successfully applied in the detection of Ag + in water samples. The study also opens a new avenue for the fabrication of functional metal nanoclusters that hold great promise in potential applications such as nanosensors, biocatalysts and molecular carriers.